Principal Leadership Strategy of Pedagogical Competence Aspect in Improving Teacher Performance of SMA Negeri 1 Singkep - Lexminader B. K. A. Doda; Encik Abdulhajar; Zaitun; Dody Irawan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to describe: 1) the plan and implementation of the principal's leadership strategy in the pedagogical competency aspect in improving teacher performance; 2) improving teacher performance in the pedagogical competency aspect. This study employs a descriptive-qualitative method, implemented at SMA Negeri 1 Singkep during the 2025/2026 academic year. The respondents of this study were the principal and compulsory subject group A teachers who teach in class X. Data on the principal's leadership strategy in the pedagogical competency aspect were collected using participatory observation guidelines, interview guidelines, and documentation instruments. In contrast, data on teacher performance in the pedagogical competency aspect were collected using portfolio instruments and questionnaires that were compiled objectively and systematically to meet the requirements of validity and reliability. The research data were analyzed thematically and qualitatively, based on the triangulation of tools, time, and sources. The results of the study: 1) the principal's leadership strategy in improving teacher performance to improve teacher performance in the pedagogical aspect can be implemented accordingly, namely: pedagogical competency development programs, quality academic supervision, and providing supporting resources and facilities for teachers; 2) there was a very significant increase in teacher performance in the pedagogical aspect through the principal's leadership strategy.